Cytotoxic Effect of Saffron Stigma Aqueous Extract on Human Prostate Cancer and Mouse Fibroblast Cell Lines: Cytotoxic Effect of Saffron Stigma Aqueous Extract in Human Prostate Cancer and Mouse Fibroblast Cell Lines - Ahmadnia, Hassan; Tavakkol Afshari, Jalil; Tabeshpour, Jamshid; Younesi Rostami, Mehdi; Mansourian, Ehsan; Akhavan Rezayat, Alireza; Brook, Azam (Urology Journal, 2020)
Purpose: Several lines of experimental evidence have shown that saffron has anticarcinogenic effects. This study aimed at evaluating the possible anticancer effect of saffron stigma aqueous extract on human prostate cancer (PC3) and mouse fibroblast cells (L929) as non-cancerous control cells. Materials and Methods: Saffron stigma aqueous extract at concentrations of 100, 200, 400, 600, 800, 1600 and 3200 μg/mL were prepared. PC3 and L929 cells were incubated with different concentrations of saffron extracts in different time intervals (24, 48, 72, 96 and 144 hours). MTT assay was used for each cell line to investigate the cytotoxic effect of saffron. Morphological alterations were also observed under light inverted microscope. Results: In fibroblast cell line after 24 hours, Saffron extract did not affect significantly the normal cells and they were intact in morphologic view. After 96 hours in the cells with highest concentration (1600 μg/mL), cell death and cellular form changes as well as severe granulation was observed. In prostate cell line after 24 hours, the only changes were observed in cells with the concentration of 1600 μg/mL. The cells were granulated and the form of the cells were spherule. After 72 hours, in group with the concentration of 1600 μg/mL, severe granulation was observed and the cell count decreased and some cells were dead. Conclusion: Saffron aqueous extract has an in vitro inhibitory effect on the proliferation of human prostate cell and mouse L929 cells which is dose-dependent.